Pemilihan Lahan Budidaya Tanaman Alpukat Menggunakan Metode Additive Ratio Assessment (ARAS) - M. Ari Prayogo (Journal of Information System Research (JOSH), 2022)
The problem in this study is that the selection of avocado cultivation land still uses the method and does not use a computer-based system to choose avocado cultivation priorities. Because it has not used a computer-based system to choose land priorities, the purpose of this study is to build a system by implementing a decision support system for selecting avocado cultivation land using the Additive Ratio Assessment (ARAS) method. The criteria parameters used to choose alternative avocado cultivation land consist of temperature, rainfall, dry month length, soil texture, and drainage. The use of these 5 criteria can choose the priority of avocado cultivation land. The results of the application of the system, that of the 7 alternative lands are in the top priority with rank 1, namely Tanah Grogot land with a Ki value of 0.895 based on the analysis of the calculation of the Additive Ratio Assessment (ARAS) method. From these results, the implementation of a decision support system using the Additive Ratio Assessment (ARAS) method can be used as the best solution for selecting priority areas for avocado cultivation.